Foreign trade and the gender earnings differential in urban Mexico - Gautam Hazarika; Rafael Otero (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper examines the effect of foreign trade induced product market competition, upon workplace gender discrimination in urban Mexico as measured by the gender earnings differential. More than four decades ago, Becker argued that labour market discrimination was economically inefficient in that discriminating firms must forego a quantity of profit. Thus, firms with more market power, i.e., firms facing less competition, may be more likely to discriminate. It therefore follows that competition in product markets may reduce discrimination in labour markets. The spread of foreign trade has traditionally been a major factor in increased product market competition. Hence, Becker's thesis suggests foreign trade will reduce employment discrimination. This paper does find evidence of a negative relation between foreign trade linked competition in product markets and workplace gender discrimination in data from the Mexican National Urban Employment Survey (Encuesta National de Empleo Urbano).
Keywords: F14; J16; J70; 330; gender discrimination; trade liberalization; Mexico; Außenhandelsliberalisierung; Lohndifferenzierung; Stadt; Mexiko; Geschlechterdiskriminierung